PENENTUAN DISTRIBUSI UKURAN PARTIKEL TEPUNG TERIGU DENGAN MENGGUNAKAN METODE PENGAPUNGAN BATANG (BUOYANCY WEIGHING-BAR METHOD) - Rondang Tambun; Nofriko Pratama; Ely; Farida Hanum (Talenta Publisher (Universitas Sumatera Utara), 2015)
Particle size measurement of wheat flour is important in wheat flour industry. There are several methods have been used to measure particle size distribution (PSD) of wheat flour, such as Andreasen pipette method, sedimentation balance method, centrifugal sedimentation method. The disadvantages of these methods are that they are time consuming and require special skills. On the other hand, PSD can be analyzed using a different principle through laser diffraction/scattering methods, and coulter counter method. The laser diffraction/scattering and coulter counter methods produce highly accurate results within a shorter time, but the equipment is extremely expensive. Therefore, a simple and cost-effective new method to determine PSD is in high demand. In this study, we aim to develop a new method to measure the particle size distribution of wheat flour using a buoyancy weighing–bar method. In this method, the density change in a suspension due to particle migration (wheat flour) is measured by weighing buoyancy against a weighing–bar hung in the suspension (etanol/metanol), and the PSD is calculated using the length of the bar and the time–course change in the mass of the bar. This apparatus consists of an analytical balance with a hook for underfloor weighing, and a weighing–bar, which is used to detect the density change in suspension. The result obtained show that the PSD of wheat flour measured by the buoyancy weighing-bar method is comparable to that determined by settling balance method.